Strategi Implementasi Pembangunan Zona Integritas pada Kantor Kementerian Agama Kabupaten Pekalongan - Ahmad Sirin (Balai Diklat Keagamaan Semarang, 2021)
This study aims to describe and analyze strategies in realizing the implementation of integrity zone development as part of the bureaucratic reform program. This study uses descriptive qualitative methods with data collection techniques through interviews, observation and secondary data collection in the form of statistical data, reports and legal documents. Determination of informants by purposive sampling on employees of the Ministry of Religion of Pekalongan Regency. The data were analyzed against the answers of the interviewees with secondary data obtained and verification of the validity of the data was carried out using triangulation techniques. The results of the study indicate that the Integrity Zone Development Implementation Strategy can be achieved by fulfilling all the indicators of the lever component and the outcome component. These indicators are proven by evidence or Evaluation Worksheets (LKE) which will be assessed by the Assessment Team for the construction of the integrity zone. In addition, a strategy is needed in the form of exemplary leadership, human resources, facilities and infrastructure, socialization and monitoring and evaluation.